Combine Effect of Tribal Black Tablet and Tribal Black Hair Oil in the Management of Khalitya (Hair Fall) open level Randomized Clinical Trial: Efficacy of Tribal Black Tablet and Tribal Black Hair Oil in Mitigating Hair Fall (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Hair fall has been emerging as a global issue during past few decades. It is although a healthissue but affects the cosmetic appearance of individuals. The natural crown that enhances the adorningappearance of the people especially the teenagers and young adults, “Hair” has been lost by fewindividuals due to various life style disturbances. According to Ayurveda vitiation of Vata and PittaDosha leads to Khalitya which has been closely related with Hair fall. Ayurveda classics have offeredefficacious herbs that correct this annoyance caused due to hair fall. One such combination has beenprepared by combination of some wonderful herbs Tribal Black Tablet and Tribal Black Hair Oil forcuring Hair fall. Thirty patients were enrolled and oral consumption of Tribal Black Tablet along withapplication Tribal Black Hair Oil was administered for thirty days. The patients were also advised toavoid oily and spicy diet, the results were observed according to the subjective, objective criteria andobservations by patient themselves. The results were markedly significant with improvement of their hairtexture as well. Patients were highly satisfied by the improvement in their hair quality and the resultsregarding hair fall and re-growth of lost hairs